Investment perspectives: Approach in the real estate sector compared to the opportunity cost of the financial market - Dozza, Marcos Antonio; Silva, João Gilberto Noleto Perna da; Dall'Agnol, Rafael Ferreira (Seven Editora, 2023)
The attributions of investment evaluation methods and their perspectives, enable the necessary knowledge for the flexibility in decisions making regarding the best investment. As a primary factor of this study, it is to be able to bring the importance and relevance of investment evaluation, its methods and techniques for making safe decisions. The approach was in the real estate sector compared to the oppor-tunity cost of the fixed income financial market. When evaluating the financial viabil-ity of an investment, there will be doubts when making decisions regarding the defi-nition of which is the best investment, or if it is acceptable, therefore, the evalua-tions must be carried out using methods and techniques that demonstrate the rates and the expected payback period of the investment, as well as its profitabil-ity and current value. DOI:https://doi.org/10.56238/sevened2023.006-037